The non-conveyance of trauma patients in Swedish emergency medical services: a retrospective observational study of the trauma population not transported to an emergency department - Glenn Larsson; Jana Eldh; Elisabeth Hagman; Magnus Andersson Hagiwara (BMC Emergency Medicine, 2024)
Abstract Introduction Due to a systemic modification in Swedish emergency medical services (EMS) staffing in recent years, the nature of the Swedish EMS has changed. Transport to an emergency department (ED) is no longer the only option. Referrals and non-conveyance form a growing part of EMS assignments. Trauma is one of the most common causes of death and accounts for 17% of Swedish EMS assignments. The aim of this study was to describe the characteristics and clinical outcomes of non-conveyed trauma patients who were assessed, treated and triaged by the EMS to gain a better understanding of, and to optimise, transport and treatment decisions. Methods The study had a descriptive, retrospective and epidemiologic design and was conducted by reviewing EMS and hospital records for 837 non-conveyed trauma patients in the southwest of Sweden in 2019. Results Three in four non-conveyed trauma patients did not seek further medical care within 72 h following EMS assessment. The patients who were admitted to hospital later were often older, had suffered a fall and had a medical history. Half of all the incidents occurred in a domestic environment, and head trauma was the major complaint. Less than 1% of the studied patients died. Conclusion Most of the non-conveyed trauma patients did not seek further medical care after being discharged at the scene. Falling was the most common trauma event, and for the older population, this meant a higher risk of hospital admission. The reasons for falls should therefore be investigated thoroughly prior to non-conveyance decisions. Future studies should focus on the reasons for non-conveyance and measure the morbidity and invalidity outcomes rather than mortality.